Copper foil and preparation method thereof, lithium battery copper foil, current collector, pole piece, battery and electric device

The copper foil prepared by electrolysis solves the problem of difficult to take into account the tensile strength and elongation of traditional lithium battery copper foil by controlling the grain fitting of the elliptical main diameter and using specific electrolyte additives, achieving efficient battery manufacturing and improving the cycleability and safety of the battery.

CN119654447AActive Publication Date: 2025-03-18JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480002653.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Traditional lithium-ion copper foils are difficult to have high tensile strength and high elongation, which leads to easy strip breakage and wrinkle breakage during battery manufacturing and use, affecting the cycle and safety of the battery.

Method used

Copper foil is prepared by electrolytic method, and the grain fitting elliptical main diameter of the copper foil is controlled to be in the range of 0.1 μm to 6.5 μm. It is combined with an appropriate amount of brightener, leveling agent and mover to optimize the crystal structure and mechanical properties of the copper foil.

Benefits of technology

It significantly improves the elongation of copper foil, which has a high tensile strength and high elongation, reduces the risk of breaking and wrinkling during manufacturing and use, and improves the cycleability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654447A_ABST
    Figure CN119654447A_ABST
Patent Text Reader

Abstract

The invention relates to a copper foil and a preparation method thereof, a lithium battery copper foil, a current collector, a pole piece, a battery and an electric device. The copper foil is provided with a first surface and a second surface which are opposite to each other, the glossiness of the first surface is Gs1, the glossiness of the second surface is Gs2, Gs1 is greater than Gs2, the main diameter of a crystal grain fitting ellipse of a cross-section crystal structure between the first surface and the second surface is recorded as phiED, the unit is [mu] m, and the phiED satisfies the following conditions: phiED = 2 * sqrt (a2 + b2), and phiED is 0.1 [mu] m-6. 5 [mu] m; wherein a and b are respectively a long radius and a short radius obtained by fitting an ellipse. The copper foil has high tensile strength and high elongation, can reduce fracture and wrinkling of the copper foil in the manufacturing process and the battery manufacturing and using process, and improves the cyclicity and safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to copper foil and a preparation method thereof, lithium battery copper foil, current collector, pole piece, battery and electrical device. Background Art

[0002] As a green and environmentally friendly energy storage device, lithium batteries have the advantages of high energy density, excellent cycle performance, and high safety. They have become a key support for industries such as electronic devices, power tools, large-scale energy storage, and new energy vehicles. They are an important basic technology for achieving the "dual carbon" goals.

[0003] As the carrier of negative electrode active materials in lithium-ion batteries and the collector and transmitter of anode electron flow, lithium battery copper foil is a key auxiliary material in the components of lithium-ion batteries. According to different application fields, lithium battery copper foil can be divided into two categories: power battery and non-power battery (such as 3C, energy storage, etc.). In the context of global carbon emission reduction, it not only promotes the rapid development of new energy industries such as new energy vehicles and photovoltaic industries, but also drives the rapid increase in demand for lithium battery copper foil.

[0004] With the rapid update and iteration of new energy technologies and equipment electronics, higher requirements are placed on the performance and safety of lithium-ion batteries, which are the core of energy storage systems. Similarly, the demand for high-performance lithium battery copper foil has intensified. Among them, tensile strength and elongation are important performance indicators of lithium battery copper foil, but traditional lithium battery copper foil is difficult to have both high tensile strength and high elongation, and it is in urgent need of improvement. Summary of the invention

[0005] Based on this, the present invention provides a copper foil and a preparation method thereof, a lithium battery copper foil, a current collector, a pole piece, a battery and an electrical device. The copper foil has both high tensile strength and high elongation, and can be used as a lithium battery copper foil to improve battery performance.

[0006] The technical solution is as follows:

[0007] A copper foil having a first surface and a second surface opposite to each other, the glossiness of the first surface is Gs1, the glossiness of the second surface is Gs2, Gs1>Gs2, and the main diameter of the grain fitting ellipse of the cross-sectional crystal structure between the first surface and the second surface is Φ ED , in μm, the Φ ED satisfy:

[0008] Φ ED =2*sqrt(a 2 +b 2 ), and Φ ED 0.1μm~6.5μm;

[0009] Among them, a and b are the major radius and minor radius obtained by fitting the ellipse, respectively.

[0010] In one embodiment, the uniformity of the grain structure in the copper foil is denoted by Γ GM , in μm, the Γ GM satisfy:

[0011] And Γ GM 0.04μm~0.30μm;

[0012] Where n is the number of grains.

[0013] In one embodiment, the proportion of twin grain boundaries in the copper foil grain structure is 55% to 75%.

[0014] In one of the embodiments, the proportion of twinned grain regions in the grain structure of the copper foil is ≥ 95%.

[0015] In one embodiment, the tensile strength of the copper foil is 30 kgf / mm at room temperature. 2 ~40kgf / mm 2 .

[0016] In one of the embodiments, at room temperature, the elongation at break of the copper foil is ≥8%.

[0017] In one embodiment, the numerical ratio of the Vickers hardness to the elongation at break of the copper foil is ψ, and ψ is less than 10.

[0018] The present invention also provides a method for preparing the copper foil as described above, and the technical scheme is as follows:

[0019] A method for preparing the copper foil as described above comprises the following steps:

[0020] The copper foil is prepared by an electrolytic method, wherein the electrolyte used in the electrolytic method includes the following components:

[0021] Copper ion 70g / L~110g / L, sulfuric acid 90g / L~130g / L, chloride ion 10ppm~30ppm, brightener 10ppm~90ppm, leveler 2ppm~25ppm and moving agent 1ppm~40ppm;

[0022] Wherein, the brightener includes a sulfur-containing group compound, the leveler includes a nitrogen-containing compound, and the displacement agent includes a polyether compound and a nitrogen-containing heterocyclic compound.

[0023] In one embodiment, the sulfur-containing group compound includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, isothiourea propane sulfonic acid inner salt and sodium 3-(benzothiazole-2-mercapto)-propane sulfonate.

[0024] In one embodiment, the nitrogen-containing compound includes one or more of collagen, gelatin, 2-amino-4-methylbenzothiazole and 2-mercaptopyridine.

[0025] In one of the embodiments, the displacement agent is prepared by compounding a polyether compound and a nitrogen-containing heterocyclic compound in a concentration ratio of 1:(1-5).

[0026] In one embodiment, the polyether compound includes one or more of polyethylene glycol and polypropylene glycol.

[0027] In one embodiment, the molecular weight of polyethylene glycol is 4000-8000.

[0028] In one embodiment, the nitrogen-containing heterocyclic compound includes polyvinyl pyrrolidone.

[0029] In one embodiment, the temperature of the electrolyte is 40°C to 70°C.

[0030] In one embodiment, the current applied during the electrolysis process is 15000A to 60000A.

[0031] The present invention also provides the application of the above copper foil, and the technical solution is as follows:

[0032] A lithium battery copper foil comprises the copper foil as described above or a copper foil prepared according to the method for preparing the copper foil as described above.

[0033] In one embodiment, the lithium battery copper foil further includes a first anti-oxidation layer and a second anti-oxidation layer, wherein the first anti-oxidation layer is stacked on the first surface of the copper foil, and the second anti-oxidation layer is stacked on the second surface of the copper foil.

[0034] In one embodiment, the first anti-oxidation layer and the second anti-oxidation layer independently include one or more of chromic anhydride, glucose and nitride.

[0035] A current collector comprises the lithium battery copper foil as described above.

[0036] A pole piece comprises the current collector as described above.

[0037] A battery comprises the pole piece as described above.

[0038] An electrical device comprises the battery as described above.

[0039] The present invention has at least the following beneficial effects:

[0040] The main diameter of the grain fitting ellipse in the copper foil interface crystal structure is Φ ED , when Φ ED When the particle size is less than 0.1 μm, the grain size is too small, the grain boundary density increases, the tensile strength increases, but the plastic deformation decreases, and the elongation decreases; on the contrary, when Φ ED If the diameter is greater than 6.5 μm, the grain size is too large, the grain boundary density is reduced, and the limited space in the crystal is difficult to accommodate the movement and accumulation of a large number of dislocations, resulting in increased internal stress, decreased tensile strength, and increased risk of tearing and breaking during copper foil manufacturing and pole piece preparation. ED The thickness of the copper foil is 0.1 μm to 6.5 μm, which can significantly improve the elongation of the copper foil, so that the copper foil has both high tensile strength and high elongation. It can reduce the phenomenon of broken foil and / or wrinkling during the copper foil manufacturing process and / or during the battery cell process and use, and improve the cycle and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is an EBSD photo of the cross section of the copper foil prepared in Example 1;

[0042] Figure 2 This is a photo of the hardness indentation of the first glossy surface (first surface, deposition surface) of the copper foil prepared in Example 2;

[0043] Figure 3 This is the EBSD photo of the copper foil cross section prepared in Comparative Example 1. DETAILED DESCRIPTION

[0044] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0046] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0047] The words "preferably", "more preferably", "preferably", "better", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the statement of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention. That is, in the present invention, "preferably", "more preferably", "preferably", "better", etc. are only used to describe implementation methods or examples with better effects, but do not constitute a limitation on the scope of protection of the present invention.

[0048] In the present invention, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.

[0049] In the present invention, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multilayer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present invention, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0050] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0051] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0052] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0053] In the present invention, "above" or "below" includes the number itself. For example, "below 1" includes 1.

[0054] In the present invention, room temperature refers to 0°C to 40°C, including but not limited to 10°C to 40°C, or further 20°C to 30°C.

[0055] Tensile strength and elongation are important performance indicators of lithium battery copper foil. The tensile strength of traditional lithium battery copper foil is 300MPa~400MPa, which has reached a relatively high level, but the elongation is only between 4% and 8%. However, in the production process of the downstream lithium battery industry, the thickness of the copper foil is required to be thinner and thinner, and the coating speed is getting faster and faster. At the same time, in the coating, rolling, baking and other battery cell processes, the copper foil will be in a high temperature and high pressure environment, which requires the copper foil to have a higher elongation to prevent dents, wrinkles or broken belts during the battery cell process, reducing production efficiency. In addition, lithium-ion batteries need to be accompanied by the expansion and contraction of active materials during charging and discharging. High-elongation copper foil can prevent the active material from falling off and breaking during the contraction and expansion of the pole piece caused by charging and discharging, thereby increasing the internal resistance and reducing the battery capacity, cycle life and safety.

[0056] In view of the problem that traditional lithium battery copper foil is difficult to have both high tensile strength and high elongation, the present invention provides a copper foil with both high tensile strength and high elongation, which can be used as lithium battery copper foil to improve battery performance.

[0057] The technical solution is as follows:

[0058] A copper foil having a first surface and a second surface opposite to each other, the glossiness of the first surface is Gs1, the glossiness of the second surface is Gs2, Gs1>Gs2, and the main diameter of the grain fitting ellipse of the cross-sectional crystal structure between the first surface and the second surface is Φ ED , in μm, the Φ ED satisfy:

[0059] Φ ED =2*sqrt(a 2 +b 2 ), and Φ ED 0.1μm~6.5μm;

[0060] Among them, a and b are the major radius and minor radius obtained by fitting the ellipse, respectively.

[0061] When the main diameter of the grain-fitting ellipse in the cross-sectional crystal structure of the copper foil surface interface is less than 0.1 μm, the copper foil grains are too small, the grain boundary density increases, the strength increases, but the plastic deformation decreases, and the elongation decreases. Grain boundaries, as surface defects commonly found in polycrystalline materials, can serve as defect nucleation sources and hinder the movement of defects. The essence of fine grain strengthening in metallurgy is the interaction between grain boundaries and dislocations, which hinders the movement of dislocations, improves strength while ensuring good plastic deformation capacity, and this process does not change the properties of the overall grain boundaries, but the disordered structure of the grain boundaries makes it difficult for dislocations to slide along them. However, there is a critical grain size. When the grain size is smaller than the critical grain size, the action of the grain boundaries inhibits the activation of the dislocation source, resulting in a reduction in plastic deformation due to the lack of movable dislocation sources and difficulty in slipping during the deformation process. In addition, when the main diameter of the grain-fitting ellipse on the surface of the copper foil is greater than 6.5 μm, the grain size of the copper foil is too large, the grain boundary density is reduced, and the limited space in the crystal is difficult to accommodate the movement and accumulation of a large number of dislocations, resulting in increased internal stress, decreased strength, and increased risks of tearing and breaking during the manufacture and use of the copper foil. The copper foil provided by the present invention has a Φ ED The thickness of the copper foil is 0.1 μm to 6.5 μm, which can significantly improve the elongation of the copper foil, so that the copper foil has both high tensile strength and high elongation, and reduces the phenomenon of broken tape and / or wrinkled copper foil during the copper foil manufacturing process and / or during the battery cell process and use.

[0062] In addition, studies have shown that the elongation of copper foil is positively correlated with thickness fitting, and the cycling stability of the battery can be improved by about 5% for every 1% increase in the elongation of copper foil at break. If the elongation of copper foil can be further improved while the thickness is reduced, it will open up a new track for the copper foil and battery industry. According to the scheme of the present invention, the elongation of copper foil can be significantly improved, thereby significantly improving the cycling and safety of the battery.

[0063] In one embodiment, the uniformity of the grain structure in the copper foil is denoted by Γ GM , in μm, the Γ GM satisfy:

[0064] And Γ GM 0.04μm~0.30μm;

[0065] Where n is the number of grains.

[0066] Γ GMIt is the ratio of the area to the perimeter of the grain-fitting ellipse of the copper foil cross section, which can be used to quantify the morphology and crystal structure of the grains. When metal materials are subjected to tensile stress, from elastic deformation to plastic deformation until fracture, materials with uniform crystal structures and materials with non-uniform crystal structures may have similar tensile strengths, but metal materials with non-uniform crystal structures will fracture early during the stretching process, that is, compared with metal materials with non-uniform crystal structures, metal materials with uniform crystal structures have a longer tensile plateau period. On the one hand, due to the presence of coarse grains and fine grains with large size differences in materials with non-uniform crystal structures, with the increase of strain, the low-angle grain boundaries in the coarse grains gradually increase, and the lattice distortion in the adjacent areas of the coarse grains and fine grains increases, while with the increase of strain, the number of lattice distortions in the uniform crystal structure increases, but the distribution is relatively uniform. Similarly, with the increase of strain, the uneven surface of the fine grain area of ​​the non-uniform microstructure will cause stress concentration. With the continuous increase of load, slip increases, and the uneven area is more distributed in the area near the coarse grain surface and the fine grain surface. In the tensile process of the uniform microstructure, the formation of the uneven area is more random and dispersed, so in the deformation process, the area with the largest difference in the non-uniform crystal structure is more likely to form strain concentration and develop into cracks, so it breaks earlier. On the other hand, the slip system between adjacent grains of the uniform crystal structure material is strain compatible, and dislocations are more likely to transfer between two pairs of grains. On the contrary, the dislocations between grains in the non-uniform crystal structure cannot be transferred between these grains or the dislocation movement is blocked. Therefore, under the same macroscopic strain conditions, the dislocation movement on both sides of the local area of ​​the non-uniform crystal structure material is asynchronous, and the coordinated strain capacity varies greatly, resulting in uneven deformation, strain asynchrony and fracture, and a decrease in plastic deformation capacity.

[0067] It has been found that when the grain structure uniformity of the copper foil cross section is Γ GM <0.04μm, the grain boundary surface is uneven, stress concentration is prone to occur, and the grain boundary density increases, which inhibits the activation of dislocation sources, making it difficult for slip to proceed, resulting in reduced plastic deformation and low elongation; the grain structure uniformity of the copper foil cross section Γ GM >0.30μm, the grain size is too large, the grain boundary density is reduced, the stress in the crystal is increased, the space for accommodating dislocations in the crystal is limited, and the strength is reduced, resulting in tearing and breaking of the copper foil during the manufacturing and use process. GM The thickness of the copper foil is 0.04 μm to 0.30 μm, including but not limited to 0.04 μm, 0.06 μm, 0.08 μm, 0.10 μm, 0.15 μm, 0.20 μm, 0.25 μm or 0.30 μm. The copper foil meeting this requirement has both high tensile strength and high elongation, and can avoid tearing and breaking of the copper foil during manufacturing and use.

[0068] Furthermore, in the crystal structure, twin grains are closely related to the mechanical properties of metal materials. Since twins can react with dislocations at the interface, they can effectively hinder the movement of dislocations. In addition, the twin interface serves as the slip plane of face-centered cubic (FCC) stacked metal materials. Not only can dislocations move on the twin interface, but the coherent grain boundary can also provide storage space for dislocations generated during the deformation process, thereby effectively improving the elongation of the copper foil.

[0069] In one embodiment, the proportion of twin grain boundaries in the grain structure of the copper foil described in the present invention is 55% to 75%, including but not limited to 55%, 60%, 65%, 70% or 75%. The copper foil that meets this requirement has both high tensile strength and high elongation, and can avoid tearing and breaking of the copper foil during manufacturing and use.

[0070] In one embodiment, the proportion of twin grain areas in the grain structure of the copper foil of the present invention is ≥95%, including but not limited to 95%, 96%, 97%, 98% or 99%. The copper foil that meets this requirement has both high tensile strength and high elongation, and can avoid tearing and breaking of the copper foil during manufacturing and use.

[0071] In one embodiment, at room temperature (such as 0°C to 40°C, further 10°C to 40°C, further 25°C), the tensile strength of the copper foil is 30 kgf / mm 2 ~40kgf / mm 2 Including but not limited to 30kgf / mm 2 、32kgf / mm 2 、34kgf / mm 2 、36kgf / mm 2 、38kgf / mm 2 or 40kgf / mm 2 Copper foil that meets this requirement can reduce the phenomenon of copper foil breaking during the preparation process and the battery cell preparation process, improve the efficiency of copper foil manufacturing and battery production, and improve the capacity and safety performance of the battery.

[0072] In one embodiment, under room temperature (such as 0°C to 40°C, further 10°C to 40°C, further 25°C), the elongation at break of the copper foil is ≥8%, including but not limited to 8%, 10%, 12%, 15%, 18% or 20%. If the elongation at break of the copper foil is less than 8%, when it is used as a lithium battery copper foil current collector, when the battery active material uses a material with a high expansion rate, during the charge and discharge process of the lithium secondary battery, the pole piece will rupture or break due to insufficient elongation with the expansion of the battery cell volume, which increases the internal resistance and reduces the capacity, cycle life and safety of the battery.

[0073] Furthermore, from the perspective of the material's microstructure and deformation mechanism, in metal materials, hardness is mainly determined by the hindering effect of the grain interface and the resistance to dislocation movement. If the ratio of the Vickers hardness of copper foil to the elongation at break is too high, the metal material has high hardness, the interaction between the grain boundary and the dislocation, and the disordered structure of the grain boundary make it difficult for the dislocation to slide along it, and the resistance to the movement of the grain boundary and dislocation is greater. At the same time, the grain boundary inhibits the activation of the dislocation source, and the material is more difficult to undergo plastic deformation under stress, resulting in a decrease in elongation.

[0074] In one embodiment, the Vickers hardness of the copper foil of the present invention is above 40 Hv. Furthermore, the Vickers hardness of the copper foil of the present invention is above 45 Hv, which is relatively high in hardness and wear-resistant.

[0075] In one embodiment, the numerical ratio of the Vickers hardness to the elongation at break of the copper foil of the present invention is ψ (for example, if the Vickers hardness of the copper foil is 48.7 Hv and the elongation at break is 15.7%, then ψ is 48.7 / 15.7=3.1), ψ<10, including but not limited to 1, 2, 3, 4, 5, 6, 7, 8 or 9. The copper foil that meets this requirement has both high tensile strength and high elongation, and can avoid tearing and breaking of the copper foil during manufacturing and use.

[0076] In one embodiment, the thickness of the copper foil is 6 μm to 12 μm, and further 8 μm to 10 μm. It can be understood that for electrolytic copper foil, the thickness of the copper foil can be controlled by the current and line speed during the preparation process.

[0077] It is understandable that the present invention does not impose any special restrictions on the method of analyzing the crystal structure of the copper foil cross section, and conventional characterization and analysis methods in the art can be used. Optionally, the present invention uses backscatter diffraction (EBSD) testing to characterize the grain structure of the copper foil of the present invention. Further, a C-Swift EBSD detector manufactured by Oxford Instruments in the United Kingdom is used to observe and characterize the crystal structure of each embodiment and comparative example sample. In order to clearly observe the grain boundary profile of the sample, the cross section is polished for 20 minutes using an ion mill in advance. Further, The n in the figure is the grain count detected by EBSD on the cross section of the copper foil. In one embodiment of the present invention, it is the number of grains in the entire field of view at a field magnification of 3000, which can be directly detected and counted by the Aztec Crystal software. In short, it is the total number of grains seen in the field of view at a magnification of 3000 when observing the cross section of the copper foil.

[0078] It is understandable that the present invention does not impose any special restrictions on the test method for the tensile strength and elongation of the copper foil, and the conventional test method in the art can be used. Optionally, in an embodiment of the present invention, according to the test method of GB / T29847-2013, a HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. is used to test the tensile strength and elongation of the sample at room temperature and a strain rate of 50 mm / min.

[0079] It is understandable that the present invention does not impose any special restrictions on the Vickers hardness test method of the copper foil, and the conventional test method in the art can be used. Optionally, in an embodiment of the present invention, the Vickers hardness (HV) test is based on the GB / T 4340.1-2009 test method, using a touch screen micro Vickers hardness tester manufactured by Shanghai Taishuo Testing Instrument Co., Ltd., and testing the Vickers hardness value (HV) of the sample at room temperature and using a 50g pressure value for 5s. Repeat the measurement of five different positions of the sample and take the average value as the final Vickers hardness value (HV) of the sample.

[0080] The present invention also provides a method for preparing the copper foil as described above, and the technical scheme is as follows:

[0081] A method for preparing the copper foil as described above comprises the following steps:

[0082] The copper foil is prepared by an electrolytic method, wherein the electrolyte used in the electrolytic method includes the following components:

[0083] Copper ion 70g / L~110g / L, sulfuric acid 90g / L~130g / L, chloride ion 10ppm~30ppm, brightener 10ppm~90ppm, leveler 2ppm~25ppm and moving agent 1ppm~40ppm;

[0084] Wherein, the brightener comprises a sulfur-containing group compound, the leveler comprises a nitrogen-containing compound, and the displacement agent comprises a polyether compound.

[0085] In the process of forming copper foil by electrolytic deposition, the phenomenon of preferential orientation (texture) will occur due to the different growth rates of each crystal plane. From the perspective of crystallography, it is generally believed that the texture growth along the (220) plane is conducive to the improvement of elongation. The present invention uses an organic composite electrolyte additive to enable the copper sulfate electrolyte to obtain relatively large and uniform grains during the deposition process, which is also conducive to the improvement of elongation. Specifically, in the present invention, a certain proportion of brightener, leveler and displacement agent are added to the electrolyte (or plating solution) as organic additives, which can change the deposition rate of copper foil and improve the mechanical properties of copper foil. Among them, the brightener is mainly composed of sulfur-containing group compounds, and its main function is to promote the nucleation of copper ions; the leveler is mainly composed of nitrogen-containing compounds, which can promote the face-centered growth of copper foil grains and make the grains flatter; when the organic sulfide brightener and nitrogen-containing compound (such as nitrogen-containing polymer) leveler are used together, the copper foil crystal structure is flatter and denser, and a large number of nanocrystalline areas are produced, which enhances the fine grain strengthening effect. The fine crystal and nano twin structure interact with each other to improve the tensile strength of the copper foil and the elongation. The positioning agent is mainly composed of ether compounds and nitrogen-containing heterocyclic compounds, which can form a more stable and uniform barrier layer, thereby effectively limiting certain growth directions of copper crystals, and interacting with other additives uniformly in various parts of the copper foil to make the grains smaller and more uniform. In addition, polyether compounds can effectively inhibit the growth of grains at high temperatures, reduce the size of grain nucleation, generate more interfaces, absorb and release thermal stress, and improve the stability of copper foil under high temperature conditions. It is understandable that some compounds have multiple functions, such as 2-amino-4-methylbenzothiazole can be used as a leveling agent and a moving agent.

[0086] In one embodiment, the sulfur-containing group compound includes one or more of sodium polydisulfide propane sulfonate (SPS), sodium 3-mercapto-1-propane sulfonate (MPS), isothiourea propane sulfonic acid inner salt (UPS) and sodium 3-(benzothiazole-2-mercapto)-propane sulfonate (ZPS). Further, the brightener is compounded from sodium polydisulfide propane sulfonate and sodium 3-mercapto-1-propane sulfonate. Further, the brightener is compounded from sodium polydisulfide propane sulfonate and sodium 3-mercapto-1-propane sulfonate in a concentration ratio of (0.5 to 3): 1.

[0087] In one embodiment, the nitrogen-containing compound includes one or more of collagen, gelatin, 2-amino-4-methylbenzothiazole and 2-mercaptopyridine.

[0088] In one of the embodiments, the displacement agent is prepared by compounding a polyether compound and a nitrogen-containing heterocyclic compound in a concentration ratio of 1:(1-5).

[0089] In one embodiment, the polyether compound includes one or more of polyethylene glycol (PEG) and polypropylene glycol (PPG). Further, the molecular weight of the polyethylene glycol is 4000-8000.

[0090] In one embodiment, the nitrogen-containing heterocyclic compound is polyvinylpyrrolidone (PVP).

[0091] In one embodiment, the positioning agent includes at least polyethylene glycol. The positioning agent is a compound of polyethylene glycol and a nitrogen-containing heterocyclic compound, which can form a more stable and uniform barrier layer, thereby effectively limiting certain growth directions of copper crystals, and interacting evenly with other additives on various parts of the copper foil, making the grains finer and more uniform, improving the uniformity of the grains, and making the copper foil have both high tensile strength and high elongation, thereby avoiding tearing and breaking of the copper foil during manufacturing and use.

[0092] In one embodiment, the temperature of the electrolyte is 40°C to 70°C.

[0093] In one embodiment, the current applied during the electrolysis process is 15000A to 60000A.

[0094] In one embodiment, the method for manufacturing the copper foil as described above comprises the following steps:

[0095] The copper plate and / or copper wire with a purity of more than 99.8% is used as raw material, high-temperature air is introduced, and the copper plate and / or copper wire are dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then the copper sulfate electrolyte is obtained through three-stage filtration; then the insoluble material is used as the anode, and the cathode roller with a titanium ring as the roller surface is used as the cathode, and the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte in the electrolytic cell, and the cathode roller rotates at a constant speed for electrolysis, and the amount of copper foil electrodeposition on the surface of the cathode roller is controlled according to the cathode current density and the cathode roller speed; after the copper foil is rotated out of the liquid surface with the roller, it is continuously peeled off from the cathode roller, and the original foil is generated after anti-oxidation, drying, and winding. The electrolyte includes the following components: copper ions 70g / L-110g / L, sulfuric acid 90g / L-130g / L, chloride ions 10ppm-30ppm, brightener 10ppm-90ppm, leveler 2ppm-25ppm and moving agent 1ppm-40ppm.

[0096] It can be understood that for copper foil prepared by electrolysis, during the preparation process, for the copper foil, the deposition surface with high gloss is the rough surface (corresponding to the first surface described in the present invention), and the roller surface that is in direct contact with the cathode roller surface and has low gloss is the glossy surface (corresponding to the second surface described in the present invention).

[0097] The present invention also provides the application of the above copper foil, and the technical solution is as follows:

[0098] (1) A lithium battery copper foil, comprising the copper foil as described above or the copper foil prepared according to the method for preparing the copper foil as described above. It can be understood that the lithium battery copper foil has the advantages of the copper foil described in the present invention, with uniform grains, moderate grain size, high tensile strength and high elongation, thereby reducing the breakage and wrinkling of the lithium battery copper foil during the manufacturing process and during the manufacturing and use of the battery, and improving the cycle performance and safety of the battery.

[0099] In one embodiment, the lithium battery copper foil further includes a first anti-oxidation layer and a second anti-oxidation layer, wherein the first anti-oxidation layer is stacked on the first surface of the copper foil, and the second anti-oxidation layer is stacked on the second surface of the copper foil.

[0100] In one embodiment, the first anti-oxidation layer and the second anti-oxidation layer independently include one or more of chromic anhydride, glucose and nitride. It can be understood that the first anti-oxidation layer and the second anti-oxidation layer of the present invention are independent of each other, so the material and dosage ratio of the first anti-oxidation layer can be the same or different from the material and dosage ratio of the second anti-oxidation layer.

[0101] (2) A current collector, comprising the lithium battery copper foil as described above. It can be understood that the current collector has the advantages of the lithium battery copper foil described in the present invention, and has both high tensile strength and high elongation, thereby reducing the breakage and wrinkling of the battery cell during the manufacturing and use process, and improving the cycle performance and safety of the battery. In one example, after the battery cell is cyclically charged and discharged, the tensile strength of the current collector is 30kgf / mm 2 ~40kgf / mm 2 , elongation ≥3%.

[0102] (3) A pole piece, comprising the current collector as described above. It can be understood that the pole piece has the advantages of the current collector described in the present invention, and has both high tensile strength and high elongation, thereby reducing the breakage and wrinkling of the battery cell during manufacturing and use, and improving the cycle performance and safety of the battery.

[0103] Furthermore, the pole piece includes a first active material layer, a current collector, and a second active material layer which are stacked. Furthermore, the first active material layer at least includes a combination of one or more of graphite materials, silicon materials, and alloy materials, and the second active material layer at least includes a combination of one or more of graphite materials, silicon materials, and alloy materials. It can be understood that in the present invention, the first active material layer and the second active material layer are independent of each other, and the raw materials, dosage ratios, and layer thicknesses used by each can be the same or different, without special restrictions.

[0104] In one embodiment, the pole piece is an anode pole piece.

[0105] (4) A battery comprising the electrode as described above.

[0106] (5) An electrical device, comprising the battery as described above. It is understandable that the electrical device is a conventional electrical device in the art, including but not limited to digital products, lighting products, cars, etc.

[0107] Specific embodiments are listed below to illustrate the present invention.

[0108] 1. The test method is as follows:

[0109] (1) EBSD test: The crystal structure of each embodiment and comparative example sample was observed and characterized using a C-Swift EBSD detector manufactured by Oxford Instruments, UK. In order to clearly observe the grain boundary profile of the sample, the cross section was polished for 20 minutes using an ion milling machine in advance, and the observation magnification was 3000 times. n is the total number of grains observed in the copper foil cross section at 3000 times the field of view, a and b are the long radius and short radius obtained by fitting the ellipse, respectively, and the average Φ ED The value refers to the average of the main diameters of the n grain fitting ellipses detected under a 3000x field of view.

[0110] (2) Tensile strength and elongation test: According to the test method GB / T29847-2013, the HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. was used to test the tensile strength and elongation of the sample at room temperature and a strain rate of 50 mm / min. The tensile test specimen is a strip specimen with a distance of 50 mm between the clamps. The sample is measured ten times and the average value is taken as the final tensile strength and elongation of the sample. Specifically, the measured tensile strength and elongation are the average values ​​of the transverse and longitudinal directions. Five copper foil strips with a size of 15*100 mm are cut in the transverse and longitudinal directions. The tensile strength and elongation of the sample are tested at room temperature and a strain rate of 50 mm / min, and the average value of a total of 10 copper foil strips in the transverse and longitudinal directions is taken as the final tensile strength and elongation value of the sample.

[0111] (3) Vickers hardness (HV) test: According to the test method GB / T4340.1-2009, the Vickers hardness value (HV) of the sample was tested at room temperature and with a pressure of 50 g for 5 seconds using a touch screen micro Vickers hardness tester manufactured by Shanghai Taishuo Testing Instrument Co., Ltd. Repeat the measurement at five different locations of the sample and take the average value as the final Vickers hardness value (HV) of the sample.

[0112] 2. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions shall be followed. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0113] Example 1

[0114] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 40ppm SPS and 45ppm MPS, the moving agent is composed of 10ppm PEG and 20ppm PVP, and the PEG molecular weight is 4000, and the leveling agent is 5ppm gelatin, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated to 43m 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0115] Three rolls of 2000m copper foil were produced in batches, and three samples of the full-width original foil were taken. After baking at 150°C for 10 minutes, the tensile strength, elongation and hardness of the copper foil were tested. The test results are shown in Table 1.

[0116] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0117] Example 2

[0118] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 45ppm SPS and 40ppm MPS, the moving agent is composed of 7ppm PEG and 25ppm PVP, and the PEG molecular weight is 4000, and the leveling agent is 5ppm gelatin, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0119] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, tensile strength, elongation and hardness tests were carried out. The test results are shown in Table 1.

[0120] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0121] Example 3

[0122] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 45ppm SPS and 30ppm MPS, the moving agent is composed of 7ppm PEG and 25ppm PVP, and the PEG molecular weight is 4000, and the leveling agent is 10ppm gelatin, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0123] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, tensile strength, elongation and hardness tests were carried out. The test results are shown in Table 1.

[0124] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0125] Example 4

[0126] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 40ppm SPS and 40ppm UPS, the moving agent is composed of 7ppm PEG and 20ppm PVP, and the PEG molecular weight is 6000, and the leveling agent is 5ppm collagen, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0127] Three rolls of 2000m copper foil were produced in batches, and three samples of the full-width original foil were taken. After baking at 150°C for 10 minutes, the tensile strength, elongation and hardness of the copper foil were tested. The test results are shown in Table 1.

[0128] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0129] Example 5

[0130] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 45ppm UPS and 40ppm ZPS, the moving agent is composed of 5ppm PEG and 20ppm PVP, and the PEG molecular weight is 8000, and the leveling agent is composed of 6ppm collagen and 3ppm gelatin. After dilution, add them to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated to 43m3 / s through the bottom pipe of the electrolytic cell. 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0131] Three rolls of 2000m copper foil were produced in batches, and three samples of the full-width original foil were taken. After baking at 150°C for 10 minutes, the tensile strength, elongation and hardness of the copper foil were tested. The test results are shown in Table 1.

[0132] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0133] Example 6

[0134] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 45ppm ZPS and 35ppm MPS, the moving agent is composed of 10ppm PEG and 15ppm PVP, and the PEG molecular weight is 8000, and the leveling agent is 10ppm gelatin, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated to 43m 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0135] Three rolls of 2000m copper foil were produced in batches, and three samples of the full-width original foil were taken. After baking at 150°C for 10 minutes, the tensile strength, elongation and hardness of the copper foil were tested. The test results are shown in Table 1.

[0136] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0137] Comparative Example 1

[0138] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, including 25ppm SPS and 20ppm MPS as brighteners, 30ppm PEG as a moving agent with a molecular weight of 4000, and 5ppm collagen as a leveling agent, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m / s through the bottom pipe of the electrolytic cell. 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0139] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, the tensile strength, elongation and hardness were tested. The test results are shown in Table 1.

[0140] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0141] Comparative Example 2

[0142] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is 85ppm SES, the moving agent is composed of 10ppm PEG and 20ppm PVP, and the PEG molecular weight is 4000), and the leveling agent is 7ppm Jiana Green, which are diluted and added to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated to 43m through the bottom pipe of the electrolytic cell. 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0143] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, tensile strength, elongation and hardness tests were carried out. The test results are shown in Table 1.

[0144] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0145] Comparative Example 3

[0146] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, among which the brightener is composed of 60ppm SES and 20ppm ZPS, the moving agent is 25ppm PVP, and the leveling agent is composed of 5ppm collagen and 5ppm Jiana Green. After dilution, add them to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m through the bottom pipe of the electrolytic cell. 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0147] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, tensile strength, elongation and hardness tests were carried out. The test results are shown in Table 1.

[0148] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0149] Comparative Example 4

[0150] Copper plates and copper wires with a purity of more than 99.8% are mixed in a 1:1 weight ratio with hot air, dissolved in sulfuric acid solution to prepare copper sulfate electrolyte, and then filtered through three stages to obtain pure copper sulfate electrolyte. An insoluble material is used as the anode, and a cathode roller with a titanium ring as the roller surface is used as the cathode. In the electrolytic cell, the bottom semicircle of the cathode roller is immersed in the copper sulfate electrolyte, and a current of 35,000A is applied and the roller rotates at a constant speed for electrolysis. The copper sulfate electrolyte contains 85g / L of Cu 2+ , 105g / L sulfuric acid, 17ppm chloride ions and organic composite electrolyte additives, where the brightener is composed of 45ppm SPS and 35ppm SES, the moving agent is 25ppm PEG, and the PEG molecular weight is 4000, and the leveling agent is composed of 5ppm gelatin and 5ppm Jianna Green. After dilution, add them to the copper sulfate electrolyte. The electrolyte temperature is 55℃, and the electrolyte is heated at 43m through the bottom pipe of the electrolytic cell. 3 / h flow rate is supplied to the electrolysis system. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, treated with chromic anhydride and glucose passivation solution for anti-oxidation, dried, and rolled up to form raw foil, which is then used as lithium battery copper foil.

[0151] Three rolls of 2000m copper foil were produced in batches. Three full-width original foil samples were taken from each roll. After baking at 150°C for 10 minutes, tensile strength, elongation and hardness tests were carried out. The test results are shown in Table 1.

[0152] The first active material layer and the second active material layer of this embodiment are prepared, by weight, from 96 parts of commercially available natural graphite, 2 parts of conductive carbon black, 1.5 parts of styrene-butadiene rubber (SBR), 0.5 parts of carboxymethyl cellulose (CMC) and 210 parts of deionized water. The slurry is applied on two opposite surfaces of the lithium battery copper foil of this embodiment using a scraper, and then the anode electrode is cut into pieces through rolling and then wound with the prepared cathode electrode in the order of cathode, diaphragm and anode into a 18650 single cell and baked in an oven for 24 hours. The water content of the anode electrode is <300ppm. The lithium secondary battery electrolyte was injected into the prepared single cell, and after standing, formation, capacity division, 10 PCS 18650 batteries with a capacity of 1.1Ah were prepared. The battery was charged at a voltage of 4.2V and discharged at a voltage of 3.2V. The charge and discharge rate was 1C at room temperature (25°C). After 3000 charge and discharge cycles, the battery was disassembled with empty batteries, and the active material of the electrode was dissolved and separated with pure water to obtain the anode current collector after cyclic charge and discharge. After baking at 105°C for 10 minutes, samples were taken to measure the elongation. The test results are shown in Table 1.

[0153] The performance data of the comparative examples described above are shown in Table 1 below.

[0154] Table 1 Performance results of comparative products of various embodiments

[0155]

[0156] Figure 1 This is the EBSD photo of the copper foil cross section prepared in Example 1. Figure 1 It can be seen that the twin area is large, the grain size difference is small, the grain boundary can effectively hinder the dislocation movement, and the elongation is high.

[0157] Figure 2 This is a photo of the hardness indentation of the first glossy surface of the copper foil prepared in Example 2. Figure 2 It can be seen that the indentation is a straight-sided quadrilateral with a low diagonal length and high hardness.

[0158] Figure 3 This is the EBSD photo of the copper foil cross section prepared in Comparative Example 1. Figure 3 It can be seen that the grain size difference is large, there are a large number of fine grains locally, and the grain boundary density is too large, which easily forms strain concentration and develops into cracks, resulting in low elongation.

[0159] In summary, the copper foil provided by the present invention has moderate grain size, good uniformity, moderate grain boundary density, high tensile strength and high elongation, and high hardness, which can reduce the phenomenon of broken foil and / or wrinkling during the copper foil manufacturing process and / or during the battery cell process and use, thereby improving the cycle performance and safety of the battery.

[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0161] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A copper foil, characterized in that: The copper foil has a first surface and a second surface opposite to each other, the glossiness of the first surface is Gs1, the glossiness of the second surface is Gs2, Gs1>Gs2, and the main diameter of the grain fitting ellipse of the cross-sectional crystal structure between the first surface and the second surface is φ ED , in μm, the φ ED satisfy: φ ED = 2 * sqrt(a 2 + b 2 ), and φ ED is from 0.1 μm to 6.5 μm; Among them, a and b are the major radius and minor radius obtained by fitting the ellipse, respectively.

2. The copper foil according to claim 1, characterized in that The uniformity of the grain structure in the copper foil is Γ GM , in μm, the Γ GM satisfy: and Γ GM is from 0.04 μm to 0.30 μm; Where n is the number of grains.

3. The copper foil according to claim 1, characterized in that The copper foil satisfies one or more of the following (1) to (2): (1) In the grain structure, the proportion of twin grain boundaries is 55% to 75%; (2) In the grain structure, the proportion of twinned grain area is ≥95%.

4. The copper foil according to any one of claims 1 to 3, characterized in that The copper foil satisfies one or more of the following (1) to (2): (1) Under room temperature conditions, the tensile strength of the copper foil is 30 kgf / mm 2 ~40kgf / mm 2 ; (2) Under room temperature conditions, the elongation at break of the copper foil is ≥8%.

5. The copper foil according to any one of claims 1 to 3, characterized in that The numerical ratio of the Vickers hardness to the elongation at break of the copper foil is ψ, and ψ is less than 10.

6. A method for preparing the copper foil according to any one of claims 1 to 5, characterized in that: The steps include: The copper foil is prepared by an electrolytic method, wherein the electrolyte used in the electrolytic method includes the following components: Copper ion 70g / L~110g / L, sulfuric acid 90g / L~130g / L, chloride ion 10ppm~30ppm, brightener 10ppm~90ppm, leveler 2ppm~25ppm and moving agent 1ppm~40ppm; Wherein, the brightener includes a sulfur-containing group compound, the leveler includes a nitrogen-containing compound, and the displacement agent includes a polyether compound and a nitrogen-containing heterocyclic compound.

7. The preparation method according to claim 6, characterized in that: Satisfy one or more of the following (1) to (5): (1) The sulfur-containing group compound includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, isothiourea propane sulfonic acid inner salt and sodium 3-(benzothiazole-2-mercapto)-propane sulfonate; (2) The nitrogen-containing compound includes one or more of collagen, gelatin, 2-amino-4-methylbenzothiazole and 2-mercaptopyridine; (3) The moving agent is prepared by compounding a polyether compound and a nitrogen-containing heterocyclic compound in a concentration ratio of 1:(1-5); (4) The polyether compound includes one or more of polyethylene glycol and polypropylene glycol; (5) The nitrogen-containing heterocyclic compound includes polyvinyl pyrrolidone.

8. The preparation method according to claim 6 or 7, characterized in that: Satisfy one or more of the following (1) to (2): (1) The temperature of the electrolyte is 40°C to 70°C; (2) The current applied during the electrolysis process is 15000A to 60000A.

9. A lithium battery copper foil, characterized in that: The invention comprises the copper foil according to any one of claims 1 to 5 or the copper foil prepared by the method for preparing the copper foil according to any one of claims 6 to 8.

10. A current collector, characterized in that: Including the lithium battery copper foil as described in claim 9.

11. A pole piece, characterized in that: Comprising the current collector according to claim 10.

12. A battery, characterized in that: Including the pole piece as claimed in claim 11.

13. An electrical device, characterized in that: Comprising the battery as claimed in claim 12.

Citation Information

Patent Citations

  • Ultrathin multi-layer structure type nano twin crystal copper foil as well as preparation method and application thereof

    CN114908386A

  • Copper foil, preparation method therefor and use thereof

    WO2024124374A1